1996
DOI: 10.1111/j.1442-2026.1996.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of magnesium in atrial fibrillation and flutter with a rapid ventricular rate

Abstract: A prospective, randomised, placebo controlled, double blinded trial to assess the efficacy of intravenous magnesium sulphate (20mmol over 30 minutes) versus placebo in patients presenting to the emergency department with rapid atrial fibrillation and flutter. The end points were slowing of the ventricular rate and reversion to sinus rhythm. A total of 41 patients were enrolled. The mean decrease in heart rate 30 minutes after commencing the infusion was 24.1/min for the magnesium group compared to 11.0/min for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…In a placebo-controlled RCT similar to ours, Walker et al 5 investigated the acute effects of magnesium in AF and flutter with a rapid ventricular rate. They gave MgSO 4 20 mmol IV over 30 minutes to 21 patients and placebo to another 20 patients.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a placebo-controlled RCT similar to ours, Walker et al 5 investigated the acute effects of magnesium in AF and flutter with a rapid ventricular rate. They gave MgSO 4 20 mmol IV over 30 minutes to 21 patients and placebo to another 20 patients.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported a fall in heart rate in patients with AF from a mean (±SD) of 130-140 (±20-30) beats ⁄ min to about 100 beats ⁄ min after treatment with MgSO 4 and using a heart rate < 100 beats ⁄ min as an endpoint. [3][4][5][6][7][8] Based on these reports, we estimated that just over 20 patients were needed in each of the two treatment groups in our study to detect a differential fall in mean (±SD) ventricular rate from 125 to 100 (±25) beats ⁄ min at 2 hours after starting the trial drugs. Calculation was based on a comparison of two means posttreatment with power set at 90% and level of significance at 5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 10 included trials involved data from six countries and all were published in English (table 1). Three trials involved patients in the emergency department,21 23 24 three trials involved patients in the intensive care unit,17 20 27 and three trials involved patients in the cardiology department or ward 22 25 26. One trial did not specify the hospital location of the patients in the trial 28.…”
Section: Resultsmentioning
confidence: 99%